State of Forests of the Caucasus and Central Asia - United Nations (United Nations, 2019)
This study presents the forest resources and the forest sector of the region, including trends in, and pressures on the resource, to describe the policies and institutions for the forest sector in the region and to list the major challenges the sector faces, and the policy responses in place or planned. It is a cooperative effort by the author, the UNECE/FAO secretariat and national experts, done with the use of the best available data. It covers all dimensions of sustainable forest management and includes national profiles of all countries of the region.